Aquicultura no Brasil : bases para um desenvolvimento sustentável - Assad, Luís Tadeu (2000)
SUSTAINABLE AQÜACULTURE. For centuries researchers have been warning about problems with our growth model. Events on both local and global scale have shown concern with mankind's destiny, thus making the sustainable development principie stronger and more consistent. This principie changes the development concept and searches for balance between this factor and the planet limits. The present chapter analyzes, in an integrated way, the economical, social, ecological and politicoinstitutional dimensions of sustainable Aquaculture. As far as Aquaculture is concerned, this new concept has been recently discussed, following the models of other human activities and having, as a reference, national and intemational conventions such as: FAO Code for responsible fisheries and Agenda 21 (National and International). However, as an emerging activity in Brazil, Aquaculture shows some particularities such as institutional lackof definition, information and a fairly rapid growth, which altogether may affect the activity's sustainability. Regarding the green revolution that is observed in the fields with the agricultural evolution, a comparison is made with the "blue revolution" that besides being incorporated to the present concept of sustainability might result in apositive balance of its benefits. As for the ecological dimension, one concludes that aquaculture is highly dependent on the environment and may be regarded as an impact activity, threatening its own sustainability. In this chapter, we describe information, examples and concepts for the useof water, land, energy, biological diversity, chemical products, trophic energy and waste reduction. As for the economical dimension, the possibilities of the activity are discussed as well as the relationship to the externai effects and its feasibility. The concept of "blue revolution" is also discussed when compared with evolution and results of the green revolution in Brazil and "The Law of Diminishing Returns", globalization and multidisciplinary effects. From the social viewpoint, the possibilities of job and income generation through Aquaculture are compared with those of otheractivities, as well associai and cultural problemsalready observed in some áreas. In this manner, small scale activity associated with large enterprises which generate market, technology and infrastructure, as well as a wide professional training, education and development of associations are essential. The political-institutional dimension transcends ali others. This chapter discusses the need of a public sector as a conflict regulator and promoter of sustainable activity. It is observed that the situation regarding public policies for the activity in Brazil is particularly serious. The roles must be defined, aiming at transparency of actions, and involvement of society as a whole in this sustainable development of aquaculture. The final considerations emphasize that we must change from a "country with potential" to a country of realities. Thus, one must search the basis of sustainable development, integrating ali mentioned dimensions and, in the Brazilian case, observing deficiencies of public policies. Finally, the activity, although highly environment dependent, presents risks and opportunities, and the public sector is responsible for minimizing the risk and negative impact, as well as maximizing advantages and benefits, believing that this could be the best moment for Aquaculture.